Casablanca - Curtiz, Michael, 1888-1962.; Burnett, Murray; Bogart, Humphrey, 1899-1957.; Bergman, Ingrid, 1915-1982.; Henreid, Paul.; Greenstreet, Sydney; Lorre, Peter; Burnett, Murray; Warner Bros. Pictures; MGM/UA Home Video (Firm) (Culver City, Calif. : MGM/UA Home Video, 1988)
A woman must choose between escaping with her husband from Nazi controlled Vichy France territory, Morocco, or staying behind with her ex-lover.
Videocassette release of the 1943 motion picture.
Based on an unproduced play, "Everybody comes to Rick's," by Murray Burnett and Joan Alison.
Producer, Hal B. Wallis ; director, Michael Curtiz ; screenplay, Julius J. Epstein, Philip G. Epstein, and Howard Koch ; music, Max Steiner ; director of photography, Arthur Edeson; film editor, Owen Marks.
Humphrey Bogart, Ingrid Bergman, Paul Henreid, Sydney Greenstreet, Peter Lorre.
VHS.
Closed-captioned.
Keywords: World War, 1939-1945 -- Drama; Feature films; Films for the hearing impaired; War films